The Impact of Vulnerability and Shocks on the Poor : The GUAPA Program in Guatmala - Tesliuc, Emil (World Bank, Washington, DC, 2012)
The Guatemala Poverty Assessment (GUAPA) report was part of a broader, multi-year program of analytical work and technical assistance that signals the commitment of the World Bank to poverty reduction and seeks to: (a) contribute to filling the crucial information gaps on poverty and living conditions; (b) deliver timely outputs on a regular and on-going basis in response to the Government's requests and data availability; and (c) provide longer-term partnering and collaboration on poverty analysis and strategy. One of the major components of the study examined how the limited assets of the poor make them particularly vulnerable to adverse shocks. In the wake of recent shocks in Guatemala (Hurricane Mitch in 1998, the recent coffee crisis, droughts and deaths from extreme acute malnutrition), the issue of vulnerability has taken center stage in policy discussions. As such, the World Bank conducted a Risk and Vulnerability Assessment (RVA) as part of the broader GUAPA. The RVA brings a "vulnerability lens" to poverty analysis. Instead of a passive, reactive approach (given poverty, what can be done to reduce it?), it takes a dynamic, proactive approach (given vulnerability, poverty and risks, what can be done to get help poor people escape poverty and reduce the likelihood that others will fall into poverty?). Using a combination of qualitative and quantitative data, the RVA analyzed both vulnerability to shocks and vulnerable groups.